Selective Killing of Cancer Cells by Nonplanar Aromatic Hydrocarbon‐Induced DNA Damage. Issue 21 (16th September 2019) - Zhou, Yan; Gan, Fuwei; Zhang, Yuanliang; He, Xiaozhen; Shen, Chengshuo; Qiu, Huibin; Liu, Peifeng
Abstract: A large number of current chemotherapeutic agents prevent the growth of tumors by inhibiting DNA synthesis of cancer cells. It has been found recently that many planar polycyclic aromatic hydrocarbons (PAHs) derivatives, previously known as carcinogenic, display anticancer activity through DNA cross‐linking. However, the practical use of these PAHs is substantially limited by their low therapeutic efficiency and selectivity toward most tumors. Herein, the anticancer property of a nonplanar PAH named [4]helicenium, which exhibits highly selective cytotoxicity toward liver, lung cancer, and leukemia cells compared with normal cells, is reported. Moreover, [4]helicenium effectively inhibits tumor growth in liver cancer‐bearing mice and shows little side effects in normal mice. RNA sequencing and confirmatory results demonstrate that [4]helicenium induces more DNA damage in tumor cells than in normal cells, resulting in tumor cell cycle arrest and apoptosis increment. This study reveals an unexpected role and molecular mechanism for PAHs in selectively killing tumor cells and provides an effective strategy for precision cancer therapies. Abstract : Nonplanar polycyclic aromatic hydrocarbons (PAH) [4]helicenium selectively kills cancer cells and efficiently inhibits tumor growth, and has no obvious side effect on normal cells. This study provides a distinctive pathway for the use of nonplanar PAHs for the treatment of tumors.